Evaluation of no evidence of progression or active disease (NEPAD) in patients with primary progressive multiple sclerosis in the ORATORIO trial. Issue 4 (16th October 2018) - Wolinsky, Jerry S.; Montalban, Xavier; Hauser, Stephen L.; Giovannoni, Gavin; Vermersch, Patrick; Bernasconi, Corrado; Deol‐Bhullar, Gurpreet; Garren, Hideki; Chin, Peter; Belachew, Shibeshih; Kappos, Ludwig
Abstract : Objective: No evidence of progression or active disease (NEPAD) is a novel combined endpoint defined by the absence of both progression and inflammatory disease activity in primary progressive multiple sclerosis (PPMS). In the placebo‐controlled phase III ORATORIO study (NCT01194570), we investigated the effect of ocrelizumab on this comprehensive outcome and its components in a post‐hoc analysis. Methods: The proportion of patients with NEPAD (no evidence of progression [NEP; no 12‐week confirmed progression of ≥1/≥0.5 points on the Expanded Disability Status Scale if the baseline score was ≤5.5/>5.5 points, respectively; no 12‐week confirmed progression of ≥20% on the Timed 25‐Foot Walk test and 9‐Hole Peg Test], no brain magnetic resonance imaging activity [no new/enlarging T2 lesions and no T1 gadolinium‐enhancing lesions], and no protocol‐defined relapse) from baseline to week 120 was determined in ocrelizumab‐ (600 mg; n = 465) and placebo‐treated (n = 234) patients. Results: The majority of ORATORIO study patients with PPMS experienced clinical progression or evidence of disease activity. From baseline to week 120, 29.9% and 42.7% ocrelizumab‐treated compared to 9.4% and 29.1% placebo‐treated patients maintained NEPAD (relative risk [95% confidence interval CI], 3.15 [2.07–4.79]; p < 0.001) and NEP (relative risk [95% CI], 1.47 [1.17–1.84]; p < 0.001), respectively. Effects on the individual components of both measures were consistent with the compound outcomes. Interpretation: Compared to placebo, ocrelizumab enhanced 3‐fold the proportion of PPMS patients with no evidence of either progression or inflammatory disease activity. NEPAD may represent a sensitive and meaningful comprehensive measure of disease control in patients with PPMS. Ann Neurol 2018;84:527–536